Age and performance: Fighting and uphill battle - Ostberg, D.; Pelot, T. (Olympic & Paralympic Coach, 2020)
Getting older is inevitable for everyone. Older athletes tend to be more disciplined in how they care for themselves, for this reason, older athletes are often described as being more professional. This describes how they approach their daily discipline toward eating, training and recovering. Most older athletes professionalized their approach out of necessity. At some point, they got injured, they felt as if they weren`t recovering as fast as they used to, or their performance began to slip. Eventually, with the change in their daily approach, they found they were able to prevent or even reverse their performance and improve their tolerance to injury. Although younger athletes may feel the effects of getting older less than older athletes, it`s never too late for younger athletes to adopt strategies and behaviors that can have an influence on long-term performance. Yet many younger athletes choose to put their heads in the sand on this topic or they get to point where age eventually catches up with them and performance begins to suffer prior to taking more ownership of their physical abilities. In modern day sport, athletes are reenacting efforts similar to the late Ponce de Leon. They are on the hunt for the mythical Fountain of Youth as well. They are in pursuit of information, strategies, technologies and tools to help them ward off the impacts of age and help them train and compete later on in their athletic careers. Decades ago, competing for a national team was something someone did prior to hanging up their sport hat to pursue a professional career outside of sport. Athletes today are competing much later in their years. With smarter training strategies, factoring in athlete feedback and the implementation of good sport science, national team athletes are now making a career out of competing in their sport.